The Role of Green Sukuk in Financing Sustainable Transport and Reducing Emissions - Mustofa, Hafidz Zainul; Wahyudi, Amin (Jurnal Ekonomi Syariah Teori dan Terapan, 2025)
This study examines how green sukuk, as a sustainable financing tool, can reduce CO2 emissions by financing the sustainable transportation sector in Indonesia. This study uses a qualitative approach and content analysis techniques to investigate the contributions of funds distributed through green sukuk to different green transportation projects. The results show that green sukuk financing for the sustainable transportation sector reached IDR 34 trillion, the largest amount compared to other sectors, such as renewable energy and water management. Financing in this sector has reduced carbon emissions by more than 15 million tonnes from 2018 to 2022. In addition, green sukuk also contributes to achieving SDGs. By offering empirical data on the effects of green sukuk financing in the sustainable transportation sector on lowering CO2 emissions, this study adds to existing literature and emphasises how it helps Indonesia achieve SDGs. This study also identified limitations in data coverage and economic impact that require further exploration. Future research should adopt a more holistic approach and consider external variables that may affect the effectiveness of green sukuk. The government can increase the effectiveness of green sukuk by implementing policies that encourage its development, including providing incentives for investors and integrating smart and green city concepts as strategic steps.